2017
DOI: 10.1161/jaha.116.004161
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Transglutaminase Modulates Vascular Stiffness and Function Through Crosslinking‐Dependent and Crosslinking‐Independent Functions

Abstract: BackgroundThe structural elements of the vascular wall, namely, extracellular matrix and smooth muscle cells (SMCs), contribute to the overall stiffness of the vessel. In this study, we examined the crosslinking‐dependent and crosslinking‐independent roles of tissue transglutaminase (TG2) in vascular function and stiffness.Methods and Results SMCs were isolated from the aortae of TG2−/− and wild‐type (WT) mice. Cell adhesion was examined by using electrical cell–substrate impedance sensing and PicoGreen assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 60 publications
1
54
0
Order By: Relevance
“…Collagen cross-linking has been correlated with increases in stiffness in the context of cell seeded matrices. For instance, it has been reported that hrTGII may indirectly modulate the stiffness of cell-seeded collagen matrices by altering cellular responses 52 such as contractility 53 that are independent of its cross-linking functions. Yet, our measurements in acellular collagen-based matrices demonstrate no modification of indentation stiffness due to cross-linking by hrTGII alone.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen cross-linking has been correlated with increases in stiffness in the context of cell seeded matrices. For instance, it has been reported that hrTGII may indirectly modulate the stiffness of cell-seeded collagen matrices by altering cellular responses 52 such as contractility 53 that are independent of its cross-linking functions. Yet, our measurements in acellular collagen-based matrices demonstrate no modification of indentation stiffness due to cross-linking by hrTGII alone.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to target LOXL2, a family member more selectively expressed in pathological contexts, show promise in preclinical fibrosis models (37-39), but have so far proven disappointing in clinical trials (40). Beyond LOX family members, transglutaminase and nonenzymatic cross-linking via glycation may also contribute to collagen stabilization and matrix stiffening (41,42).…”
mentioning
confidence: 99%
“…TG2 has consistently shown an important role in age-dependent vascular stiffness 8,9,11,24,25 . In particular, Santhanam et al 8 showed that PWV measures of TG2 -/mice were similar to age-matched WT controls, but those TG2 -/were protected from the increase in PWV resulting from NOS inhibition using L-NAME 8 .…”
Section: ■ Discussionmentioning
confidence: 99%